Pengaruh Motif Berbelanja dan Atribut Toko terhadap Kepuasan Konsumen di Matahari Department Store Kota Malang - Andreas Budiarto (Jurnal Ilmiah Mahasiswa FEB, 2012)
Abstract:  This research basicly aims to know the influence of shopping motives and store attributes to customer satisfaction. The location is chosen for this research is Matahari Department Store Kota Malang. The research was done to 100 responden by using quantitative-explanatory approach. Thus, data analysis which is used is statistic analysis in the form of double linier regression test. The result of research show that the two free variable (shopping motives and store attributes) by stimulant have significant influence to customer satisfaction with test F = 23,845 (sig. 000). While influence by partial, only store attributes variable having influence impact to customer satisfaction with sig. 000 (t = 5,829). From the two free variable also found that store attributes variable represent most having on effect on customer satisfaction variable. Keywords: shopping motives, store attributes, and customer satisfaction